Philosophical Foundations of Mixed Methods Research Dialogues between Researchers and Philosophers - Shan, Yafeng (Taylor & Francis, 2024)
Philosophical Foundations of Mixed Methods Research provides a comprehensive examination of the philosophical foundations of mixed methods research. It offers new defences of the seven main approaches to mixed methods (the pragmatist approach, the transformative approach, the indigenous approach, the dialectical approach, the dialectical pluralist approach, the performative approach, and the realist approach) written by leading mixed methods researchers. Each approach is accompanied by critical reflections chapter from philosophers' point of view. The book shows the value of the use of mixed methods from a philosophical point of view and offers a systematic and critical examination of these positions and approaches from a philosophical point of view. The volume also offers a platform to promote a dialogue between mixed methods researchers and philosophers of science and provides foundations for further research and teaching of this hotly debated topic. This volume is ideal for researchers and advanced students, and anyone who is interested in research methods and the social sciences more generally.